Constructivism in Writing Learning in Elementary School; Systematic Literature Review - Sudarman, Risnandar; Damaianti, Vismaia S; Mulyati, Yeti; Setiana, Soni Mulyawan (International Journal of Research and Applied Technology (INJURATECH), 2024)
This study aims to enhance learners' writing competence in line with their individual talents and interests, structured through the stages of pre-learning, core activities, and closing. Competence development is facilitated through constructivist principles, applied during the writing process based on specific themes within various text genres. Within the constructivist framework, learners actively engage in sorting, selecting, and organizing content areas (writing topics) as a foundation for their writing. Subsequently, learners refine their work by editing, revising, and ultimately publishing their writing for reader engagement, appreciation, feedback, and assessment. This study employs a systematic literature review methodology, analyzing a total of 65 journal articles across four databases, focusing on primary school writing instruction, constructivist learning models, and their applications in writing pedagogy. The review process involved identification, primary data selection, data extraction and synthesis of results. The findings of this review will offer insights into effective instructional strategies to support writing skills development in primary school contexts, emphasizing the role of constructivism in the writing learning process.